Tropical montane cloud forests - Hamilton, Lawrence S.; Juvik, James O.; Scatena, F. N. (Ecological studies, 1995)
Until relatively recently the valuable tropical montane cloud forests of the world had scarcely come under the assaults experienced by the downslope montane and lowland forests. Increasingly, however,these cloud forest ecosystems are now being fragmented, reduced, and disturbed at an alarming rate. It is now recognized that steps must be taken rapidly to increase our understanding of these cloud forests. Tropical Montane Cloud Forests summarizes the current research from around the world on these cloud forests. This book will be of interest to plant ecologists, tropical biologists, and foresters